Influence of eco-materials on indoor air quality. Issue 2 (9th June 2016) - da Silva, Carla Florbela F. P.; Rana, Chetas; Maskell, Daniel; Dengel, Andy; Ansell, Martin P.; Ball, Richard J.
Abstract : This paper investigates the role of commercially available natural building materials, including lime mortars, natural fibres and wood panels on the indoor air quality. Initially, the emissions of volatile organic compounds (VOCs) from building materials were identified and measured. Subsequent tests then considered the adsorption and re-emission behaviour of four VOCs: toluene, limonene, dodecane and formaldehyde. The significance of this paper lies in its demonstration that emissions are dependent on the chemical composition of building materials and the production process, whereas the adsorption/desorption characteristics are related to the material microstructure and the polarity of the VOCs. The results allow the performance of a construction material, in terms of its influence on indoor air quality, to be deduced from knowledge of chemical composition and microstructure. This paper provides a new approach to assessing the influence of different building materials on indoor air quality when they are exposed to gaseous pollutants.